In Vitro Hepatoprotective Activity of Methanolic Leaf Extract of Acalypha indica Against CCl4 Induced Hepatotoxicity in Goat Liver Slice Culture - Nambiar, Mandeth Kodiyil Geetha; Varghese, Vijesh (Trends in Sciences, 2023)
Plants used in traditional medicine may constitute an important source of new biologically active compounds. Acalypha indica is one of the weed plants that contain important medicinal values for human health applications. The present study was undertaken to assess the hepatoprotective activity of methanolic leaf extract of Acalypha indica in goat liver slice culture against carbon tetrachloride (CCl4) to prove its efficacy against liver disorders CCl4 was used to induce hepatotoxicity in liver slice of goat. The cytotoxicity induced by CCl4 was estimated by quantifying the release of marker enzymes such as alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP), acid phosphatase (ACP) and lactate dehydrogenase (LDH). Also, the degree of hepatic damage was measured by estimating the levels of lipid peroxidation (LPO) of hepatocytes membrane lipids. The treatment of liver cells with CCl4 caused twice increase in LPO of cells besides release of LDH, ALT, AST, ACP and ALP by 6.55, 3.89, 3.31, 2.69 and 2.50 times, respectively as compared to untreated liver cells. Thus, a toxic effect of CCl4 was significantly reduced by the treatment of methanolic leaf extract of Acalypha indica, silymarin and quercetin. The free radical scavenging activity of plant extract was estimated by 2, 2-diphenylpicrylhydrazyl (DPPH) method and IC50 is 65.12 ± 2.27 μg/mL. Qualitative analysis of flavonoid indicates the presence of flavonoids in plant extract. These results indicate that all concentration of plant extract of Acalypha indica, silymarin and quercetin protect the liver cells from CCl4 induced oxidative/free radical mediated damage in vitro. The hepatoprotective activity of methanolic extract of Acalypha indica extract is due to the presence of flavonoids which have remarkable antioxidant and anti-inflammatory activity. HIGHLIGHTS Liver disorders are the most common health hazard found in developing countries due to dietary habits, alcohol ingestion, poor hygiene, unsupervised drug use and smoking. Liver diseases can be non-inflammatory, inflammatory and degenerative Acalypha indica is one of the weed plants that contain important medicinal values for human health applications In vitro study of methanolic leaf extract of Acalypha indica against CCl4 induced hepatic damage in goat liver slice culture proven its efficacy against liver diseases GRAPHICAL ABSTRACT